Hubungan Kadar C-Reactive Protein dengan Jumlah Leukosit Penderita Tuberkulosis Paru pada Fase Pengobatan 0 dan 2 Bulan di BKPM Purwokerto - Syafira Dian Ergiana; Dita Pratiwi Kusuma Wardani; Tantri Analisawati Sudarsono; Arif Mulyanto (Jurnal Surya Medika (JSM), 2022)
Pulmonary tuberculosis is still a health problem to control in the world. This disease is caused by the bacterium Mycobacterium tuberculosis, which can cause inflammation that can trigger increased levels of C-Reactive Protein and leukocytes in the body. This study was conducted to determine the correlation between C-Reactive Protein levels and the number of leukocytes with treatment phases 0 and 2 months in BKPM Purwokerto. The design of this study was an analytical observation with a cross-sectional research design. Results from 30 pulmonary tuberculosis patients treated for 0 and 2 months showed a correlation between CRP levels and white blood cell counts (p = 0.002, r = 0.445). There is a moderate relationship between CRP levels and leukocyte counts. High levels of CRP correlate with increasing the number of leukocytes. More research is needed on the relationship between CRP levels and leukocyte counts with different phases of treatment.